Reward does not modulate the preview benefit in visual search. Issue 4 (21st April 2021) - Mine, Chisato; Most, Steven B.; Le Pelley, Mike E.
ABSTRACT: Preview benefit refers to faster search for a target when a subset of distractors is seen prior to the search display. We investigated whether reward modulates this effect. Participants identified a target among non-targets on each trial. On "preview" trials, placeholders occupied half the search array positions prior to the onset of the full array. On "non-preview" trials, no placeholders preceded the full search array. On preview trials, the target could appear at either a placeholder position (old-target-location condition) or a position where no placeholder had been (new-target-location condition). Critically, the colour of the stimulus array indicated whether participants would earn reward for a correct response. We found a typical preview benefit, but no evidence that reward modulated this effect, despite a manipulation check showing that stimuli in the reward-signaling colour tended to capture attention on catch trials. The results suggest that reward learning does not modulate the preview benefit.